2016
DOI: 10.2174/1568026616666160414123343
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potentials of Triterpenes in Diabetes and its Associated Complications

Abstract: Diabetes is a major chronic metabolic disorder globally and around of 285 million people are affected by the disease and the number is expected to double in the next two decades. The major focus of anti-diabetic therapies is to enhance insulin production, sensitivity and/or reduce the blood glucose level. Although several synthetic drugs have been developed as antidiabetic agents but their utility has been hampered due to their side effects and poor efficacy. In this scenario, research on natural products has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 0 publications
0
35
0
1
Order By: Relevance
“…Studies have already reported that DM cannot be treated with traditional medicine alone, as it has not been able to adjust the level of glucose completely and has many side effects [20]. In this respect, research on medicinal plants has shown their importance in diabetes therapy, as toxicological studies have proven them to be the safest [20].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have already reported that DM cannot be treated with traditional medicine alone, as it has not been able to adjust the level of glucose completely and has many side effects [20]. In this respect, research on medicinal plants has shown their importance in diabetes therapy, as toxicological studies have proven them to be the safest [20].…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes mellitus (DM) is a common metabolic disease characterized by hyperglycaemia. DM suffering for a long‐term usually leads to chronic damage on eyes, kidneys, heart, blood vessels and nerves, resulting in various complications and even death . It is also worth noting that patients with DM may have decreased immune function, uncontrollable infection and delayed skin wound healing to cause or aggravate the occurrence and progress of diabetic foot or gangrene .…”
Section: Introductionmentioning
confidence: 99%
“…Terpenoids which belong to an important class of natural products and several terpenoids have been reported as anti-diabetic agents [34][35][36][37][38][39] .…”
Section: Discussionmentioning
confidence: 99%